1975
DOI: 10.3109/00016347509156739
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Imminent Premature Labour

Abstract: In this study, 194 imminent premature deliveries were treated. The pregnancies were in the 28th to 36th week. Uterine contractions were demonstrable in all patients and amniotic membranes were intact. All patients were treated with bedrest. Two betasympathomimetics were used in a double-blind study: Nyldrin hydrochloride (43 cases) and Isoxuprine hydrochloride (60 cases). A placebo was given to 41 patients, and ethyl alcohol to 50 patients. Intravenous and intramuscular treatment given in the hospital was cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, the findings on the usage of alcohol to treat threatening PTB are controversial [57-61]. In addition, the evidence for a positive effect is weak, as randomized control trials showed no effect of alcohol to prevent PTB [59-61] and the side-effects of alcohol were considered to be unacceptable [21,60]. Thus, this treatment method was abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings on the usage of alcohol to treat threatening PTB are controversial [57-61]. In addition, the evidence for a positive effect is weak, as randomized control trials showed no effect of alcohol to prevent PTB [59-61] and the side-effects of alcohol were considered to be unacceptable [21,60]. Thus, this treatment method was abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…When preterm labor is diagnosed on the basis of contractions alone, between 30% and 70% of women will resolve without treatment. 38,39 In this circumstance, many more patients would be required to determine a benefit of rofecoxib. It is likely that, despite the entry criteria, many of our patients were not in true preterm labor and the high success rate of both groups is the result of our definition of preterm labor.…”
Section: And Inflammatorymentioning
confidence: 98%
“…During the past 30 years, obstetricians have tried to arrest threatened preterm labor by use of two pharmacologically different drugs: beta(sympatho)mimetis (50,51) and prostaglandin-synthesis inhibitors such as indomethacin (52). Indometh-acin is shown to be a 20% more powerful tocolytic drug than the betamimetics (53,54), but it may cause constriction of the fetal ductus arteriosus (55) and neonatal bronchopulmonary dysplasia (56).…”
Section: New Tocolytic Agentsmentioning
confidence: 99%